Chiral Mn(III) salen complex immobilized onto ionic liquid modified mesoporous silica for oxidative kinetic resolution of secondary alcohols - Sahoo, Suman; Kumar, Pradeep; Lefebvre, F.; Halligudi, Shivaraj B. (Tetrahedron Letters, 2008)
A supported ionic liquid strategy has been applied for the immobilization of a chiral Mn(III) salen complex onto ionic liquid modified mesoporous silica SBA-15. The immobilized catalyst demonstrated high enantioselectivity and activity in the oxidative kinetic resolution of secondary alcohols, and could be recycled five times without obvious loss of activity. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Mesoporous silica SBA-15; Mn(III) salen; Oxidative kinetic resolution; Secondary alcohol; Supported ionic liquid

Enantioselective hydrogenation of olefins by chiral iridium phosphorothioite complex covalently anchored on mesoporous silica - Sahoo, Suman; Kumar, Pradeep; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Catalysis, 2008)
Chiral monodentate phosphorous-based ligands have proven effective for the enantioselective hydrogenation of olefins. Binol-derived monodentate phosphorothioite (PS) ligand was synthesized from binol and thiopropyltriethoxysilane, and its iridium complex was covalently anchored to mesoporous silica supports like SBA-15, MCM-41, and MCM-48. These catalysts were characterized by different physicochemical techniques and assessed for their catalytic performances in the heterogeneous asymmetric hydrogenation of itaconic acid and its derivatives. It was found that the catalytic activities and enantioselectivities of the heterogenized iridium complex (IrPSSBA-15) in the hydrogenation reactions were comparable to its homogeneous analogue. Binol-derived monodentate phosphorothioite ligand in heterogeneously anchored form (iridium complex) is a more effective catalyst than the reported monodentate phosphorous ligand systems in the hydrogenation reactions, possibly due to the changes in electronic properties around the iridium metal center. The effects of substrate-to-catalyst molar ratio, solvents, and temperature on substrate conversions and enantioselectivities, of the products were investigated in hydrogenation reactions. (c) 2007 Elsevier Inc. All rights reserved.
Keywords: binol; Enantioselective hydrogenation; Immobilization; iridium complex; itaconic acid; Mesoporous silica SBA-15; monodentate ligand; phosphorothioite ligand

Heteropoly acid-based supported ionic liquid-phase catalyst for the selective oxidation of alcohols - Bordoloi, Ankur; Sahoo, Suman; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Catalysis, 2008)
A supported ionic liquid strategy has been applied for the immobilization of a heteropolyacid, molybdovanadophosphoric acid, onto ionic liquid-modified mesoporous silica SBA-15. The immobilized catalyst demonstrated high activity in the aerobic oxidation of primary and secondary alcohols to aldehydes and ketones, respectively. No overoxidation of the primary alcohols to carboxylic acids was observed. Secondary alcohols were chemoselectively oxidized to ketones in the presence of primary alcohol, hetero atom, and allyl groups. This catalyst could be recycled five times without obvious loss of activity. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Air as an oxidant; Mesoporous silica SBA-15; Molybdovanadophosphoric acid; Selective oxidation; Supported ionic liquid